Hiroshi Sugimoto - gates of paradise - Sugimoto, Hiroshi 1948- (Skira Rizzoli, 2017)
In an electrifying moment in 1585, four Japanese youths appeared before Pope Gregory XIII, summoned to his court from the nascent Christian community in Japan to present themselves at the capital of their faith. Legendary photographer Hiroshi Sugimoto follows in the boys footsteps, capturing the architectural wonders of Rome, Florence, and Venice as the Eastern visitors might have seen them on their grand tour. Sugimoto's images present each chapel and theatre as a marvel, imposing and dark. He contextualizes his photographs with Japanese works from the period and the decades that follow. These panels and objects attest to the impact of Western culture, specifically Jesuit Christianity, on Momoyama and Edo aesthetics as Japanese artists envisioned scenes of European life. Exhibition: Japan Society, New York, USA (20.10.2017-07.01.2018)
"This catalogue is published on the occasion of the exhibition Hiroshi Sugimoto: Gates of Paradise, October 20, 2017-January 7, 2018, organized by Japan Society, New York"--Title page verso. - Includes bibliographical references and index
Keywords: Sugimoto, Hiroshi -- 1948-; Fotografie; Rezeption; Kunst; Japan; Sugimoto, Hiroshi 1948-; Sugimoto, Hiroshi 1948- / Exhibitions / Sugimoto, Hiroshi 1948-; Japan Society (New York, N.Y.) / Exhibitions / Japan Society (New York, N.Y.) / 2000-2099; Art, Japanese / Exhibitions / 21st century / New York (State) / New York; Photography, Artistic / Exhibitions / 21st century; Art, Japanese; Photography, Artistic / New York (State) / New York; Ausstellungskatalog -- Japan Society -- 20.10.2017-07.01.2018 -- New York, NY; Bildband